The Influence of Military Coup 2014 on Public Trust Among Student in Thai Public Services: a Case Study of Khon Kaen University Student’s Attitude - Nabilla Dzikri Azhari; Sripokangkul, Siwach; Muhammad Kamil; Tri Sulistyaningsih (Journal for Developing the Social and Community, 2020)
This study aims to determine the influence of the military coup in 2014 on public trust among students in public service Thailand. This research was conducted on Khon Kaen University students with a total sample of 31 people. The research instrument used was a questionnaire through a purposive sampling technique. Regression analysis results show that the value of tcount is 15.737 > ttable 2.04523 means that there is a positive and significant influence between the relationship of the 2014 Military Coup with Public Trust in Public Services. While the value of r count 0, 946 or Pearson Correlations in this analysis shows the direction of a positive correlation, meaning that between the Military Coup and Public Trust in Public Services has a strong relationship.